The Effect of OrganizationallJustice on Organizational CitizenshiplBehavior with Job Satisfaction as a Mediation Variable (Study on Employees of PT Jasamarga Ngawi Kertasono) - Mauriska Dearsi; Intan Ratnawati (Budapest International Research and Critics University, 2022)
The purpose of this study is to investigate the impact of organizational justice on organizational citizenship behavior and job satisfaction, as well as the impact of job satisfaction on organizational citizenship behavior and the role of job satisfaction as a mediating variable on the impact of organizational citizenship behavior on PT. Jasamarga Ngawi Kertasono employees. This study employed a cross-sectional study approach and a quantitative descriptive research design. There were 63 permanent employees used as samples in this study, out of a total of 123 permanent and contract employees at PT Jasamarga Ngawi Kertasono. With the help of SmartPLS 2.0 software, the data analysis technique used was Partial Least Square (PLS). The results indicate that organizational justice has a positive and significant impact on organizational citizenship behavior, as well as a positive and significant impact on job satisfaction and organizational citizenship behavior. Furthermore, the findings suggest that, via job satisfaction variables, organizational justice has a positive and significant impact on organizational citizenship behavior.